Vivência da equipe de enfermagem de uma instituição de longa permanência no cuidado a idosas com transtornos mentais - Saldanha, Viviane Segabinazzi (2017)
The aging of the population has the mental disorders as the most common health problems in the third age, since they affect around one-third of the elderly population. Thus, there is the search for institutions to sustain this population: the Long Term Care Institutions for the Elderly (LTIE), alternatives for the elderly who need long-term care. In this context, the study aimed to understand the experiences of nursing staff a lsiap, in the care of elderly people with mental disorders. It is a qualitative, descriptive, which was a semi-structured interview with the nursing professionals who work in a. The ethical aspects of research involving human beings were respected according to Resolution 466/12 of the National Health Council. The results were presented in five thematic axes: the care of institutionalized elderly: feelings and experiences of the nursing team; mental disorder in the perception of the nursing team; nursing team in the care of elderly people with mental disorder; the care of the nursing team in a situation of worsening of symptoms of mental disorder experienced by older people; and the institutional conditions that interfere in the care of elderly people with mental disorders. They showed that the team did not feel prepared enough to act with the elderly women with mental disorders. Noted that the presents itself as a space of constant learning for nursing professionals when faced with situations that are not planned, encouraging the search for solutions by the team itself. The aggressive behavior of older people reflected in fear of being attacked and the risk of aggression to other elderly women of the nursing team. The institutional conditions, such as the lack of personnel and the burden of nursing work were reported as factors that hinder the care more attentive and dedicated to the elderly people with mental disorders in the. It is concluded that the care requires, in addition to empirical knowledge, sensitivity and affection, adequate working conditions and professional development. Stresses the need to promote permenent education, related to aging affected by psychiatric disorders.